2020
DOI: 10.1101/2020.11.06.20222398
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Optimal test-assisted quarantine strategies for COVID-19

Abstract: BackgroundUntil herd immunity occurs for COVID-19, quarantine will remain a pillar for disease mitigation. A 14-day quarantine, although widely recommended for self-quarantine after potential infections and mandated by many government agencies can be physically and mentally stressful for those under quarantine and leads to lost productivity. Testing during quarantine is currently implemented by businesses and governments as a promising method to shorten the duration of quarantine. However, to our knowledge, no… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 61 publications
0
3
0
Order By: Relevance
“…Simulation revealed the efficacy of a 10-day, and other foreshortened, quarantine strategies. The command used for the simulation is listed under the flowchart ( Figure 3 ), and for full details of this implementation, we refer the reader to Peng et al ( 14 ).…”
Section: Resultsmentioning
confidence: 99%
“…Simulation revealed the efficacy of a 10-day, and other foreshortened, quarantine strategies. The command used for the simulation is listed under the flowchart ( Figure 3 ), and for full details of this implementation, we refer the reader to Peng et al ( 14 ).…”
Section: Resultsmentioning
confidence: 99%
“…In a populated country like India, SARS-CoV-2 testing by RT-PCR is an uphill battle since it can detect non infectious as well as dead viral paricles which lasts as positive for long period of time. 10 In this scenario, RAT can be used as SARS-CoV-2 detection point-of-care test for rapid and massive testing, despite its lower sensitivity than RT-PCR. 11 Since January 2020, three consecutive waves occurred, in Puducherry Union territory (UT) the cases In our hospital setting, we tested surveillance samples, outpatient, and in-patient samples.…”
Section: Discussionmentioning
confidence: 99%
“…Until now, asymptomatic infection tends to be identified among young people (<20 yr old) and its proportion among all confirmed cases widely differed (from 1.95% to 87.9%) ( 34 ). Isolation and close observation at home for 14 days after diagnosis are regarded as a better option for these asymptomatic infections ( 35 ), and recent findings indicated that testing during quarantine may reduce the length of isolation, decrease the physical and mental stress caused by long quarantines ( 36 ). “However, suspected and confirmed cases must be treated in isolated hospitals with effective isolation and protection conditions” ( 37 ).…”
Section: Introductionmentioning
confidence: 99%